Notes on the morphology and ecology of the adult females of Nesippus species (Siphonostomatoida: Pandaridae) with a key for identification - Dippenaar, Susan M.; Jordaan, Bea P. (Zootaxa, 2012)
Nesippus Heller, 1868 species are members of Pandaridae without dorsal plates on the second free thoracic segment. Cur-rently there are five accepted species, namely N. orientalis Heller, 1868, N. crypturus Heller, 1868, N. vespa Kirtisinghe,1964, N. tigris Cressey, 1967 and N. nana Cressey, 1970. Members of Nesippus were collected from a variety of elasmo-branch hosts caught in the nets of the Natal Sharks Board, set off the KwaZulu-Natal coast, South Africa. Of these, rep-resentatives of N. orientalis were the most cosmopolitan and commonly encountered and the easiest to identify. Specimensof N. vespa and N. tigris were fairly host specific, often encountered and also relatively easy to identify. Difficulty in theidentification of specimens of N. crypturus and N. nana is mainly due to morphological variations observed in specimensof N. crypturus which is also a relatively widely distributed species. However, the main distinguishing features of the dif-ferent species are highlighted and a key is provided to assist in the identification of the adult females. Additionally, ecological aspects like prevalence, mean intensity and mean abundance of each species are also calculated and reported.